Exercise Solutions: Functional Verification Software Testing and Verification Prepared by Stephen M. Thebaut, Ph.D. University of Florida
Exercise (from Lecture Notes #21) “Identity” function: x,y := x,y Given P = if x>=y then x,y := y,x f1 = (x>y x,y := y,x | true I) f2 = (x>y x,y := y,x | x<y I) f3 = (x≠y x,y := y,x) Fill in the following “correctness table”: P C=Complete S=Sufficient N=Neither f1 f2 f3
Exercise (from Lecture Notes #21) “Identity” function: x,y := x,y Given P = if x>=y then x,y := y,x f1 = (x>y x,y := y,x | true I) f2 = (x>y x,y := y,x | x<y I) f3 = (x≠y x,y := y,x) Fill in the following “correctness table”: P C=Complete S=Sufficient N=Neither f1 f2 f3
Exercise (from Lecture Notes #21) “Identity” function: x,y := x,y Given P = if x>=y then x,y := y,x f1 = (x>y x,y := y,x | true I) f2 = (x>y x,y := y,x | x<y I) f3 = (x≠y x,y := y,x) Fill in the following “correctness table”: P C=Complete S=Sufficient N=Neither f1 C f2 f3
Exercise (from Lecture Notes #21) “Identity” function: x,y := x,y Given P = if x>=y then x,y := y,x f1 = (x>y x,y := y,x | true I) f2 = (x>y x,y := y,x | x<y I) f3 = (x≠y x,y := y,x) Fill in the following “correctness table”: P C=Complete S=Sufficient N=Neither f1 C f2 f3
Exercise (from Lecture Notes #21) “Identity” function: x,y := x,y Given P = if x>=y then x,y := y,x f1 = (x>y x,y := y,x | true I) f2 = (x>y x,y := y,x | x<y I) f3 = (x≠y x,y := y,x) Fill in the following “correctness table”: P C=Complete S=Sufficient N=Neither f1 C S f2 f3
Exercise (from Lecture Notes #21) “Identity” function: x,y := x,y Given P = if x>=y then x,y := y,x f1 = (x>y x,y := y,x | true I) f2 = (x>y x,y := y,x | x<y I) f3 = (x≠y x,y := y,x) Fill in the following “correctness table”: P C=Complete S=Sufficient N=Neither f1 C S f2 f3
Exercise (from Lecture Notes #21) “Identity” function: x,y := x,y Given P = if x>=y then x,y := y,x f1 = (x>y x,y := y,x | true I) f2 = (x>y x,y := y,x | x<y I) f3 = (x≠y x,y := y,x) Fill in the following “correctness table”: P C=Complete S=Sufficient N=Neither f1 C S N f2 f3
Exercise (from Lecture Notes #22) Prove f = [A] where f = (x=17 x,y := 17,20 | true x,y := x,-x) and A is: if x=17 then y := x+3 else y := -x end_if_else
if_then_else Correctness Conditions Complete correctness conditions for f = [if p then G else H] (where g = [G] and h = [H] have already been shown): Prove: p (f = g) Л ¬p (f = h) Working correctness questions: When p is true, does f equal g? When p is false, does f equal h?
Proof that f = [P] f = (x=17 x,y := 17,20 | true x,y := x,-x) A: if x=17 then y := x+3 else y := -x end_if_else
Proof that f = [P] f = (x=17 x,y := 17,20 | true x,y := x,-x) A: if x=17 then y := x+3 G else y := -x H end_if_else
Proof that f = [P] f = (x=17 x,y := 17,20 | true x,y := x,-x) A: if x=17 then y := x+3 G else y := -x H end_if_else By observation, g = x,y := x,x+3 h = x,y := x,-x
Proof that f = [P] (cont’d) Therefore, by the Axiom of Replacement, it is sufficient to show: f = (x=17 x,y := 17,20 | true x,y := x,-x) = [if x=17 then (x,y := x,x+3) else (x,y := x,-x)] g p h
Proof that f = [P] (cont’d) Therefore, by the Axiom of Replacement, it is sufficient to show: f = (x=17 x,y := 17,20 | true x,y := x,-x) = [if x=17 then (x,y := x,x+3) else (x,y := x,-x)] When p is true does f equal g? When p is false does f equal h? g p h
Proof that f = [P] (cont’d) Therefore, by the Axiom of Replacement, it is sufficient to show: f = (x=17 x,y := 17,20 | true x,y := x,-x) = [if x=17 then (x,y := x,x+3) else (x,y := x,-x)] When p is true does f equal g? (x=17) (f = (x,y := 17,20)) When p is false does f equal h? g p h
Proof that f = [P] (cont’d) Therefore, by the Axiom of Replacement, it is sufficient to show: f = (x=17 x,y := 17,20 | true x,y := x,-x) = [if x=17 then (x,y := x,x+3) else (x,y := x,-x)] When p is true does f equal g? (x=17) (f = (x,y := 17,20)) (x=17) (g = (x,y := x,x+3) When p is false does f equal h? g p h
Proof that f = [P] (cont’d) Therefore, by the Axiom of Replacement, it is sufficient to show: f = (x=17 x,y := 17,20 | true x,y := x,-x) = [if x=17 then (x,y := x,x+3) else (x,y := x,-x)] When p is true does f equal g? (x=17) (f = (x,y := 17,20)) (x=17) (g = (x,y := x,x+3) = (x,y := 17,20)) When p is false does f equal h? g p h
Proof that f = [P] (cont’d) Therefore, by the Axiom of Replacement, it is sufficient to show: f = (x=17 x,y := 17,20 | true x,y := x,-x) = [if x=17 then (x,y := x,x+3) else (x,y := x,-x)] When p is true does f equal g? (x=17) (f = (x,y := 17,20)) (x=17) (g = (x,y := x,x+3) √ = (x,y := 17,20)) When p is false does f equal h? g p h
Proof that f = [P] (cont’d) Therefore, by the Axiom of Replacement, it is sufficient to show: f = (x=17 x,y := 17,20 | true x,y := x,-x) = [if x=17 then (x,y := x,x+3) else (x,y := x,-x)] When p is true does f equal g? (x=17) (f = (x,y := 17,20)) (x=17) (g = (x,y := x,x+3) √ = (x,y := 17,20)) When p is false does f equal h? (x≠17) (f = (x,y := x,-x)) g p h
Proof that f = [P] (cont’d) Therefore, by the Axiom of Replacement, it is sufficient to show: f = (x=17 x,y := 17,20 | true x,y := x,-x) = [if x=17 then (x,y := x,x+3) else (x,y := x,-x)] When p is true does f equal g? (x=17) (f = (x,y := 17,20)) (x=17) (g = (x,y := x,x+3) √ = (x,y := 17,20)) When p is false does f equal h? (x≠17) (f = (x,y := x,-x)) (x≠17) (h = (x,y := x,-x)) g p h
Proof that f = [P] (cont’d) Therefore, by the Axiom of Replacement, it is sufficient to show: f = (x=17 x,y := 17,20 | true x,y := x,-x) = [if x=17 then (x,y := x,x+3) else (x,y := x,-x)] When p is true does f equal g? (x=17) (f = (x,y := 17,20)) (x=17) (g = (x,y := x,x+3) √ = (x,y := 17,20)) When p is false does f equal h? (x≠17) (f = (x,y := x,-x)) (x≠17) (h = (x,y := x,-x)) g p h √
Exercise 1 (from Lecture Notes #23) For program M below, where all variables are integers, hypothesize a function f for [M] and prove f = [M]. while i<n do t := t*x i := i+1 end_while
Exercise 1 (from Lecture Notes #23) For program M below, where all variables are integers, hypothesize a function f for [M] and prove f = [M]. while i<n do t := t*x i := i+1 end_while Hypothesized f:
Exercise 1 (from Lecture Notes #23) For program M below, where all variables are integers, hypothesize a function f for [M] and prove f = [M]. while i<n do t := t*x i := i+1 end_while Hypothesized f: (i<n i,t :=
Exercise 1 (from Lecture Notes #23) For program M below, where all variables are integers, hypothesize a function f for [M] and prove f = [M]. while i<n do t := t*x i := i+1 end_while Hypothesized f: (i<n i,t := n,
Exercise 1 (from Lecture Notes #23) For program M below, where all variables are integers, hypothesize a function f for [M] and prove f = [M]. while i<n do t := t*x i := i+1 end_while Hypothesized f: (i<n i,t := n,txn-i
Exercise 1 (from Lecture Notes #23) For program M below, where all variables are integers, hypothesize a function f for [M] and prove f = [M]. while i<n do t := t*x i := i+1 end_while Hypothesized f: (i<n i,t := n,txn-i | i≥n
Exercise 1 (from Lecture Notes #23) For program M below, where all variables are integers, hypothesize a function f for [M] and prove f = [M]. while i<n do t := t*x i := i+1 end_while Hypothesized f: (i<n i,t := n,txn-i | i≥n I)
Exercise 1 (from Lecture Notes #23) For program M below, where all variables are integers, hypothesize a function f for [M] and prove f = [M]. while i<n do t := t*x i := i+1 end_while Hypothesized f: (i<n i,t := n,txn-i | i≥n I) Alternative f:
Exercise 1 (from Lecture Notes #23) For program M below, where all variables are integers, hypothesize a function f for [M] and prove f = [M]. while i<n do t := t*x i := i+1 end_while Hypothesized f: (i<n i,t := n,txn-i | i≥n I) Alternative f: (i≤n i,t := n,txn-i | i>n I)
Exercise 1 (from Lecture Notes #23) For program M below, where all variables are integers, hypothesize a function f for [M] and prove f = [M]. while i<n do t := t*x i := i+1 end_while Hypothesized f: (i<n i,t := n,txn-i | i≥n I) Alternative f: (i≤n i,t := n,txn-i | i>n I) Does it make any difference which we use?
while_do Correctness Conditions Complete correctness conditions for f = [while p do g] (where g = [G] has already been shown): Prove: term(f,M) Л p (f = f o g) Л ¬p (f = I)
Proof that f = [M] f = (i<n i,t := n,txn-i | i≥n I) M: while i<n do t := t*x i := i+1 end_while
Proof that f = [M] f = (i<n i,t := n,txn-i | i≥n I) M: while i<n do t := t*x i := i+1 end_while p G
Proof that f = [M] f = (i<n i,t := n,txn-i | i≥n I) M: while i<n do t := t*x i := i+1 end_while By observation, g = [G] = (i,t := i+1,tx) p G
Proof that f = [M] f = (i<n i,t := n,txn-i | i≥n I) M: while i<n do t := t*x i := i+1 end_while By observation, g = [G] = (i,t := i+1,tx) Is loop termination guaranteed for any argument in D(f)? p G
Proof that f = [M] f = (i<n i,t := n,txn-i | i≥n I) M: while i<n do t := t*x i := i+1 end_while By observation, g = [G] = (i,t := i+1,tx) Is loop termination guaranteed for any argument in D(f)? YES. (Show this using the Method of Well-Founded Sets.) p G
Proof that f = [M] (cont’d) Does (i≥n) ( f = I )?
Proof that f = [M] (cont’d) Does (i≥n) ( f = I )? ( Recall: f = (i<n i,t := n,txn-i | i≥n I) )
Proof that f = [M] (cont’d) Does (i≥n) ( f = I )? √ ( Recall: f = (i<n i,t := n,txn-i | i≥n I) )
Proof that f = [M] (cont’d) Does (i≥n) ( f = I )? √ Does (i<n) ( f = f o g )? ( Recall: f = (i<n i,t := n,txn-i | i≥n I) )
Proof that f = [M] (cont’d) Does (i≥n) ( f = I )? √ Does (i<n) ( f = f o g )? (i<n) ( f = i,t := n,txn-i ) ( Recall: f = (i<n i,t := n,txn-i | i≥n I) )
Proof that f = [M] (cont’d) Does (i≥n) ( f = I )? √ Does (i<n) ( f = f o g )? (i<n) ( f = i,t := n,txn-i ) (i<n) ( f o g = f o (i,t := i+1,tx) ) ( Recall: f = (i<n i,t := n,txn-i | i≥n I) )
Proof that f = [M] (cont’d) Does (i≥n) ( f = I )? √ Does (i<n) ( f = f o g )? (i<n) ( f = i,t := n,txn-i ) (i<n) ( f o g = f o (i,t := i+1,tx) ) What is f when applied after g changes the initial value of i? ( Recall: f = (i<n i,t := n,txn-i | i≥n I) )
Proof that f = [M] (cont’d) Does (i≥n) ( f = I )? √ Does (i<n) ( f = f o g )? (i<n) ( f = i,t := n,txn-i ) (i<n) ( f o g = f o (i,t := i+1,tx) ) What is f when applied after g changes the initial value of i? There are two cases to consider: i=n-1 & i<n-1 ( Recall: f = (i<n i,t := n,txn-i | i≥n I) )
Proof that f = [M] (cont’d) Does (i<n) ( f = f o g )? case a: (i=n-1) ( f = i,t := n,txn-i ( Recall: f = (i<n i,t := n,txn-i | i≥n I) )
Proof that f = [M] (cont’d) Does (i<n) ( f = f o g )? case a: (i=n-1) ( f = i,t := n,txn-i ( Recall: f = (i<n i,t := n,txn-i | i≥n I) )
Proof that f = [M] (cont’d) Does (i<n) ( f = f o g )? case a: (i=n-1) ( f = i,t := n,txn-(n-1) ( Recall: f = (i<n i,t := n,txn-i | i≥n I) )
Proof that f = [M] (cont’d) Does (i<n) ( f = f o g )? case a: (i=n-1) ( f = i,t := n,txn-(n-1) = i,t := n,tx ) ( Recall: f = (i<n i,t := n,txn-i | i≥n I) )
Proof that f = [M] (cont’d) Does (i<n) ( f = f o g )? case a: (i=n-1) ( f = i,t := n,txn-(n-1) = i,t := n,tx ) (i=n-1) ( f o g = f o (i,t := i+1,tx) ( Recall: f = (i<n i,t := n,txn-i | i≥n I) )
Proof that f = [M] (cont’d) Does (i<n) ( f = f o g )? case a: (i=n-1) ( f = i,t := n,txn-(n-1) = i,t := n,tx ) (i=n-1) ( f o g = ? o (i,t := i+1,tx) ( Recall: f = (i<n i,t := n,txn-i | i≥n I) )
Proof that f = [M] (cont’d) Does (i<n) ( f = f o g )? case a: (i=n-1) ( f = i,t := n,txn-(n-1) = i,t := n,tx ) (i=n-1) ( f o g = ? o (i,t := i+1,tx) ( Recall: f = (i<n i,t := n,txn-i | i≥n I) )
Proof that f = [M] (cont’d) Does (i<n) ( f = f o g )? case a: (i=n-1) ( f = i,t := n,txn-(n-1) = i,t := n,tx ) (i=n-1) ( f o g = ? o (i,t := i+1,tx) = ? o (i,t := n-1+1,tx) ( Recall: f = (i<n i,t := n,txn-i | i≥n I) )
Proof that f = [M] (cont’d) Does (i<n) ( f = f o g )? case a: (i=n-1) ( f = i,t := n,txn-(n-1) = i,t := n,tx ) (i=n-1) ( f o g = ? o (i,t := i+1,tx) = ? o (i,t := n-1+1,tx) ( Recall: f = (i<n i,t := n,txn-i | i≥n I) )
Proof that f = [M] (cont’d) Does (i<n) ( f = f o g )? case a: (i=n-1) ( f = i,t := n,txn-(n-1) = i,t := n,tx ) (i=n-1) ( f o g = ? o (i,t := i+1,tx) = ? o (i,t := n-1+1,tx) = ? o (i,t := n,tx) ( Recall: f = (i<n i,t := n,txn-i | i≥n I) )
Proof that f = [M] (cont’d) Does (i<n) ( f = f o g )? case a: (i=n-1) ( f = i,t := n,txn-(n-1) = i,t := n,tx ) (i=n-1) ( f o g = ? o (i,t := i+1,tx) = ? o (i,t := n-1+1,tx) = I o (i,t := n,tx) since gi(i=n-1) = n ( Recall: f = (i<n i,t := n,txn-i | i≥n I) )
Proof that f = [M] (cont’d) Does (i<n) ( f = f o g )? case a: (i=n-1) ( f = i,t := n,txn-(n-1) = i,t := n,tx ) (i=n-1) ( f o g = ? o (i,t := i+1,tx) = ? o (i,t := n-1+1,tx) = I o (i,t := n,tx) = (i,t := n,tx) ( Recall: f = (i<n i,t := n,txn-i | i≥n I) )
Proof that f = [M] (cont’d) Does (i<n) ( f = f o g )? case a: (i=n-1) ( f = i,t := n,txn-(n-1) = i,t := n,tx ) (i=n-1) ( f o g = ? o (i,t := i+1,tx) = ? o (i,t := n-1+1,tx) = I o (i,t := n,tx) = (i,t := n,tx) ( Recall: f = (i<n i,t := n,txn-i | i≥n I) )
Proof that f = [M] (cont’d) Does (i<n) ( f = f o g )? case a: √ (i=n-1) ( f = i,t := n,txn-(n-1) = i,t := n,tx ) (i=n-1) ( f o g = ? o (i,t := i+1,tx) = ? o (i,t := n-1+1,tx) = I o (i,t := n,tx) = (i,t := n,tx) ( Recall: f = (i<n i,t := n,txn-i | i≥n I) )
Proof that f = [M] (cont’d) Does (i<n) ( f = f o g )? case b: (i<n-1) ( f = i,t := n,txn-i ) ( Recall: f = (i<n i,t := n,txn-i | i≥n I) )
Proof that f = [M] (cont’d) Does (i<n) ( f = f o g )? case b: (i<n-1) ( f = i,t := n,txn-i ) (i<n-1) ( f o g = f o (i,t := i+1,tx) ( Recall: f = (i<n i,t := n,txn-i | i≥n I) )
Proof that f = [M] (cont’d) Does (i<n) ( f = f o g )? case b: (i<n-1) ( f = i,t := n,txn-i ) (i<n-1) ( f o g = ? o (i,t := i+1,tx) ( Recall: f = (i<n i,t := n,txn-i | i≥n I) )
Proof that f = [M] (cont’d) Does (i<n) ( f = f o g )? case b: (i<n-1) ( f = i,t := n,txn-i ) (i<n-1) ( f o g = (i,t := n,txn-i) o (i,t := i+1,tx) since gi(i<n-1) < n ( Recall: f = (i<n i,t := n,txn-i | i≥n I) )
Proof that f = [M] (cont’d) Does (i<n) ( f = f o g )? case b: (i<n-1) ( f = i,t := n,txn-i ) (i<n-1) ( f o g = (i,t := n,txn-i) o (i,t := i+1,tx) ( Recall: f = (i<n i,t := n,txn-i | i≥n I) )
Proof that f = [M] (cont’d) Does (i<n) ( f = f o g )? case b: (i<n-1) ( f = i,t := n,txn-i ) (i<n-1) ( f o g = (i,t := n,txn-i) o (i,t := i+1,tx) = (i,t := n,(tx)xn-(i+1)) ( Recall: f = (i<n i,t := n,txn-i | i≥n I) )
Proof that f = [M] (cont’d) Does (i<n) ( f = f o g )? case b: (i<n-1) ( f = i,t := n,txn-i ) (i<n-1) ( f o g = (i,t := n,txn-i) o (i,t := i+1,tx) = (i,t := n,(tx)xn-(i+1)) = (i,t := n,(tx)xn-i-1) ( Recall: f = (i<n i,t := n,txn-i | i≥n I) )
Proof that f = [M] (cont’d) Does (i<n) ( f = f o g )? case b: (i<n-1) ( f = i,t := n,txn-i ) (i<n-1) ( f o g = (i,t := n,txn-i) o (i,t := i+1,tx) = (i,t := n,(tx)xn-(i+1)) = (i,t := n,(tx)xn-i-1) = (i,t := n,txn-i-1+1) ( Recall: f = (i<n i,t := n,txn-i | i≥n I) )
Proof that f = [M] (cont’d) Does (i<n) ( f = f o g )? case b: (i<n-1) ( f = i,t := n,txn-i ) (i<n-1) ( f o g = (i,t := n,txn-i) o (i,t := i+1,tx) = (i,t := n,(tx)xn-(i+1)) = (i,t := n,(tx)xn-i-1) = (i,t := n,txn-i-1+1) = (i,t := n,txn-i) ( Recall: f = (i<n i,t := n,txn-i | i≥n I) )
Proof that f = [M] (cont’d) Does (i<n) ( f = f o g )? case b: (i<n-1) ( f = i,t := n,txn-i ) (i<n-1) ( f o g = (i,t := n,txn-i) o (i,t := i+1,tx) = (i,t := n,(tx)xn-(i+1)) = (i,t := n,(tx)xn-i-1) = (i,t := n,txn-i-1+1) = (i,t := n,txn-i) ( Recall: f = (i<n i,t := n,txn-i | i≥n I) )
Proof that f = [M] (cont’d) Does (i<n) ( f = f o g )? √ case b: √ (i<n-1) ( f = i,t := n,txn-i ) (i<n-1) ( f o g = (i,t := n,txn-i) o (i,t := i+1,tx) = (i,t := n,(tx)xn-(i+1)) = (i,t := n,(tx)xn-i-1) = (i,t := n,txn-i-1+1) = (i,t := n,txn-i) ( Recall: f = (i<n i,t := n,txn-i | i≥n I) )
Exercise 2 (from Lecture Notes #23) For program R below, where all variables are integers, hypothesize a function r for [R] and prove r = [R]. repeat: x := x−1 y := y+2 until x=0
Exercise 2 (from Lecture Notes #23) For program R below, where all variables are integers, hypothesize a function r for [R] and prove r = [R]. repeat: x := x−1 y := y+2 until x=0 Hypothesized r:
Exercise 2 (from Lecture Notes #23) For program R below, where all variables are integers, hypothesize a function r for [R] and prove r = [R]. repeat: x := x−1 y := y+2 until x=0 Hypothesized r: (x>0 x,y := ?,?
Exercise 2 (from Lecture Notes #23) For program R below, where all variables are integers, hypothesize a function r for [R] and prove r = [R]. repeat: x := x−1 y := y+2 until x=0 Hypothesized r: (x>0 x,y := 0,?
Exercise 2 (from Lecture Notes #23) For program R below, where all variables are integers, hypothesize a function r for [R] and prove r = [R]. repeat: x := x−1 y := y+2 until x=0 Hypothesized r: (x>0 x,y := 0,y+2x)
repeat_until Correctness Conditions Complete correctness conditions for f = [P] = [repeat g until p] (where g = [G] has already been shown): Prove: term(f,P) Л (p o g) (f = g) Л ¬(p o g) (f = f o g)
Proof that r = [R] r = (x>0 x,y := 0,y+2x) R: repeat: x := x−1 until x=0
Proof that r = [R] r = (x>0 x,y := 0,y+2x) R: repeat: x := x−1 until x=0 G p
Proof that r = [R] r = (x>0 x,y := 0,y+2x) R: repeat: until x=0 By observation, g = [G] = (x,y := x-1,y+2) G p
Proof that r = [R] r = (x>0 x,y := 0,y+2x) R: repeat: until x=0 By observation, g = [G] = (x,y := x-1,y+2) Is loop termination guaranteed for any argument in D(r)? G p
Proof that r = [R] r = (x>0 x,y := 0,y+2x) R: repeat: until x=0 By observation, g = [G] = (x,y := x-1,y+2) Is loop termination guaranteed for any argument in D(r)? YES. (Show this using the Method of Well-Founded Sets.) G p
Proof that r = [R] (cont’d) Does (p o g) (r = g) ? ( Recall: r = (x>0 x,y := 0,y+2x) )
Proof that r = [R] (cont’d) Does (p o g) (r = g) ? [ (x=0) o (x,y := x-1,y+2) ] ? ( Recall: r = (x>0 x,y := 0,y+2x) )
Proof that r = [R] (cont’d) Does (p o g) (r = g) ? [ (x=0) o (x,y := x-1,y+2) ] (x0=1) ( Recall: r = (x>0 x,y := 0,y+2x) )
Proof that r = [R] (cont’d) Does (p o g) (r = g) ? [ (x=0) o (x,y := x-1,y+2) ] (x0=1) (x=1) ( r = (x,y := 0,y+2x) ( Recall: r = (x>0 x,y := 0,y+2x) )
Proof that r = [R] (cont’d) Does (p o g) (r = g) ? [ (x=0) o (x,y := x-1,y+2) ] (x0=1) (x=1) ( r = (x,y := 0,y+2x) = (x,y := 0,y+2) ) ( Recall: r = (x>0 x,y := 0,y+2x) )
Proof that r = [R] (cont’d) Does (p o g) (r = g) ? [ (x=0) o (x,y := x-1,y+2) ] (x0=1) (x=1) ( r = (x,y := 0,y+2x) = (x,y := 0,y+2) ) (x=1) ( g = (x,y := x-1,y+2) ( Recall: r = (x>0 x,y := 0,y+2x) )
Proof that r = [R] (cont’d) Does (p o g) (r = g) ? [ (x=0) o (x,y := x-1,y+2) ] (x0=1) (x=1) ( r = (x,y := 0,y+2x) = (x,y := 0,y+2) ) (x=1) ( g = (x,y := x-1,y+2) ( Recall: r = (x>0 x,y := 0,y+2x) )
Proof that r = [R] (cont’d) Does (p o g) (r = g) ? [ (x=0) o (x,y := x-1,y+2) ] (x0=1) (x=1) ( r = (x,y := 0,y+2x) = (x,y := 0,y+2) ) (x=1) ( g = (x,y := x-1,y+2) √ ( Recall: r = (x>0 x,y := 0,y+2x) )
Proof that r = [R] (cont’d) Does ¬(p o g) (r = r o g) ? ( Recall: r = (x>0 x,y := 0,y+2x) )
Proof that r = [R] (cont’d) Does ¬(p o g) (r = r o g) ? ¬[ (x=0) o (x,y := x-1,y+2) ] (x0≠1) Thus, there are 2 cases to consider: x0<1 and x0>1. ( Recall: r = (x>0 x,y := 0,y+2x) )
Proof that r = [R] (cont’d) Does ¬(p o g) (r = r o g) ? ¬[ (x=0) o (x,y := x-1,y+2) ] (x0≠1) Thus, there are 2 cases to consider: x0<1 and x0>1. case a: (x<1) ( r = undefined ) ( Recall: r = (x>0 x,y := 0,y+2x) )
Proof that r = [R] (cont’d) Does ¬(p o g) (r = r o g) ? ¬[ (x=0) o (x,y := x-1,y+2) ] (x0≠1) Thus, there are 2 cases to consider: x0<1 and x0>1. case a: (x<1) ( r = undefined ) (x<1) ( r o g = undefined o g since ((x>0) o g(x<1)) = false ( Recall: r = (x>0 x,y := 0,y+2x) )
Proof that r = [R] (cont’d) Does ¬(p o g) (r = r o g) ? ¬[ (x=0) o (x,y := x-1,y+2) ] (x0≠1) Thus, there are 2 cases to consider: x0<1 and x0>1. case a: (x<1) ( r = undefined ) (x<1) ( r o g = undefined o g = undefined ) since ((x>0) o g(x<1)) = false ( Recall: r = (x>0 x,y := 0,y+2x) )
Proof that r = [R] (cont’d) Does ¬(p o g) (r = r o g) ? ¬[ (x=0) o (x,y := x-1,y+2) ] (x0≠1) Thus, there are 2 cases to consider: x0<1 and x0>1. case a: (x<1) ( r = undefined ) (x<1) ( r o g = undefined o g = undefined ) since ((x>0) o g(x<1)) = false √ ( Recall: r = (x>0 x,y := 0,y+2x) )
Proof that r = [R] (cont’d) case b: (x>1) ( r = (x,y := 0,y+2x) ) ( Recall: r = (x>0 x,y := 0,y+2x) )
Proof that r = [R] (cont’d) case b: (x>1) ( r = (x,y := 0,y+2x) ) (x>1) ( r o g = (x,y := 0,y+2x) o (x,y := x-1,y+2) since ((x>0) o g(x>1)) = true ( Recall: r = (x>0 x,y := 0,y+2x) )
Proof that r = [R] (cont’d) case b: (x>1) ( r = (x,y := 0,y+2x) ) (x>1) ( r o g = (x,y := 0,y+2x) o (x,y := x-1,y+2) since ((x>0) o g(x>1)) = true ( Recall: r = (x>0 x,y := 0,y+2x) )
Proof that r = [R] (cont’d) case b: (x>1) ( r = (x,y := 0,y+2x) ) (x>1) ( r o g = (x,y := 0,y+2x) o (x,y := x-1,y+2) since ((x>0) o g(x>1)) = true = (x,y := 0,(y+2)+2(x-1)) ( Recall: r = (x>0 x,y := 0,y+2x) )
Proof that r = [R] (cont’d) case b: (x>1) ( r = (x,y := 0,y+2x) ) (x>1) ( r o g = (x,y := 0,y+2x) o (x,y := x-1,y+2) since ((x>0) o g(x>1)) = true = (x,y := 0,(y+2)+2(x-1)) = (x,y := 0,(y+2+2x-2)) ( Recall: r = (x>0 x,y := 0,y+2x) )
Proof that r = [R] (cont’d) case b: (x>1) ( r = (x,y := 0,y+2x) ) (x>1) ( r o g = (x,y := 0,y+2x) o (x,y := x-1,y+2) since ((x>0) o g(x>1)) = true = (x,y := 0,(y+2)+2(x-1)) = (x,y := 0,(y+2+2x-2)) = (x,y := 0,y+2x) ) ( Recall: r = (x>0 x,y := 0,y+2x) )
Proof that r = [R] (cont’d) case b: (x>1) ( r = (x,y := 0,y+2x) ) (x>1) ( r o g = (x,y := 0,y+2x) o (x,y := x-1,y+2) since ((x>0) o g(x>1)) = true = (x,y := 0,(y+2)+2(x-1)) = (x,y := 0,(y+2+2x-2)) = (x,y := 0,y+2x) ) √ ( Recall: r = (x>0 x,y := 0,y+2x) )
Proof that r = [R] (cont’d) case b: (x>1) ( r = (x,y := 0,y+2x) ) (x>1) ( r o g = (x,y := 0,y+2x) o (x,y := x-1,y+2) since ((x>0) o g(x>1)) = true = (x,y := 0,(y+2)+2(x-1)) = (x,y := 0,(y+2+2x-2)) = (x,y := 0,y+2x) ) Therefore, ¬(p o g) (r = r o g) √ √ ( Recall: r = (x>0 x,y := 0,y+2x) )
Exercise Solutions: Functional Verification Software Testing and Verification Prepared by Stephen M. Thebaut, Ph.D. University of Florida